Optimization of experimental conditions and analysis tools for the study of phosphodiesterase-5 in a model of cultured adult rat cardiomyocytes - Botha, Anél (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)--Stellenbosch University, 2017